Walkability of School Surroundings and its Impact on Pedestrian Behaviour - Shbeeb, Lina; Awad, Wael (TeMA - Journal of Land Use, Mobility and Environment, 2013)
Pedestrian accident is a serious problem in Jordan. It is believedthat walking environment is a contributory factor. This study looks intopedestrian environment in schools’ vicinity. Seventeen schools were selectedand 231 students were followed from school to home. Results showed that 15% ofobserved subjects were involved in conflicts. Average walking time is 17 minutes;almost half of this time is spent either by walking on street or crossing. Femalesare involved in less conflict and they spend less time in traffic. Drivers givepriority to pedestrian in one-thirds of all observed crossing with preferenceto males.